Diagnosis of Testicular Choriocarcinoma: A Case Study - Arif, NUM; Shaikh, AU; Ranen, B; Waheed, Z (Bangladesh Medical Journal, 2014)
Testicular cancer, although relatively rare, is the most common malignancy in men at the age of 15 to 35 years. Germ cell tumor (GCT) is the most common testicular tumor (90%-95%) and peak age of incidence is between 20 years to 50 years. Choriocarcinoma is very rare in male as a pure testicular tumor (<1%) but may be seen as a component of mixed GCT. These tumors characteristically secrete hCG (human chorionic gonadotrophin) into the serum, which use as an important serum tumor marker for these tumors. A 30 years old male presented to us with the complaints of hard feeling of the left testis for 6 months which was initiated with mild pain but the size of the testis was unchanged. On examination there was an indurated area (2cm X 2cm) at lower part of the left testis and epididymis felt separately. He had no history crypto-orchidism, orchitis and scrotal trauma. Ultrasonogram showed a mixed echoic mass lesion (13 X 10mm) at infero-medial aspect left testis with an epididymal cyst. On laboratory investigation his ?-hCG and AFP level were 306 MIU/L(high) & 6.3 IU/L respectively. Contrast enhanced CT scan of the whole abdomen revealed no abnormality except enlarged lymph node (> 1 CM) in right lower lung. Fine needle aspiration cytology (FNAC) showed features of chronic orchitis. We explored his left testis because of high ?-hCG through inguinal approach and suspected testicular tissue was sent for frozen section biopsy which also revealed inconclusive findings. On the basis of his high ?-hCG, we performed left radical orchidectomy. Histopathology of the left testis showed features of Choriocarcinoma, epididymis and spermatic cord were normal. According to TNM classification, AJCC (American Joint Committee on Cancer) staging and international germ cell consensus prognostic classification it was T3N0MISI, stage IIIa and intermediate prognosis group respectively. Postorchidectomy ?-hCG dropped to 7.3 MIU/ML. Now he is on systemic chemotherapy BEP(bleomycin, etoposide, cisplatin). Choriocarcinoma, though is a rare malignancy, it may affect young men in the prime of life and is the most aggressive histologic variant of germ cell tumor. But it has a good prognosis if diagnosed early and treated accurately. Serum ?-hCG level plays most important role in diagnosis, in monitoring therapy and follow-up of patients with choriocarcinoma. DOI: http://dx.doi.org/10.3329/bmj.v40i2.18514 Bangladesh Medical Journal 2011 Vol.40(2): 60-62